2005
DOI: 10.1111/j.1365-2850.2005.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nurses’ opinion of client behaviour and level of social functioning on the amount of time they spend with clients

Abstract: The impact of nurses' opinion of client behaviour and level of social functioning on the amount of time they spend with clients For people afflicted with different kinds of psychiatric disorder, suffering is a common denominator. The time the nurses spend with psychiatric clients may mirror their attitudes towards and feelings for these clients. The aim of this study was to investigate the connections between the time spent together and the nurses' opinion of client behaviour and social functioning in communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Low social interaction between staff and nursing home residents seem to be strongly connected to cognitive impairment (Chen et al. , 2000) and an additional barrier to staff interaction is aggressive behaviour (Kristiansen et al. , 2005; Hellzén & Asplund, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low social interaction between staff and nursing home residents seem to be strongly connected to cognitive impairment (Chen et al. , 2000) and an additional barrier to staff interaction is aggressive behaviour (Kristiansen et al. , 2005; Hellzén & Asplund, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is documented knowledge that impaired residents are particularly vulnerable to low social interaction (Kelly, 1997), staff interactions outside the expected routines of resident care is still low (Norbergh et al, 2002). Low social interaction between staff and nursing home residents seem to be strongly connected to cognitive impairment (Chen et al, 2000) and an additional barrier to staff interaction is aggressive behaviour (Kristiansen et al, 2005;Hellzén & Asplund, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to reconstruct mental health nursing from institutional, nurse‐controlled care to a home‐based, client‐centred perspective are still incomplete and lack knowledge from other disciplines, such as social science and ethics (15). Furthermore, people with long‐term mental illnesses who were involved in rehabilitation programmes experienced the support as being inadequate or misdirected, indicating that the professionals were obstacles to their rehabilitation (4); the most socially and psychiatrically disabled clients tended to spend more time in solitude than their co‐clients (13,16). Taken together, the above‐mentioned studies indicate a need to clarify the professional role of nurses as they undergo a period of role re‐definition (17).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this reduction in bed numbers, many clinicians believe that inpatient care remains an essential option for times of severe distress when a patient may need constant monitoring and care (Burns & Firn 2003). Paradoxically, there is some evidence that most vulnerable and dependent individuals may receive the least staff attention following admission (Kristiansen et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most consistent complaints made by patients is that too little effort is made to engage with them (Laurence 2002). In Sweden, a study revealed that psychiatric inpatients spent an average of 60.8% of time alone, while only 20% of their daily time was spent with the nurses (Kristiansen et al . 2005) and there is little agreement in the nursing literature on how inpatient care should most effectively be structured and on the nature of the interactions/interventions that inpatient nurses should provide.…”
Section: Introductionmentioning
confidence: 99%